Relativistic intensity laser interactions with low-density plasmas - Willingale, L; Nilson, P; Zulick, C; Chen, H; Craxton, R; Cobble, J; Maksimchuk, A; Norreys, P; Sangster, T; Scott, R; Stoeckl, C (IOP Publishing, 2016)
© Published under licence by IOP Publishing Ltd. We perform relativistic-intensity laser experiments using the Omega EP laser to investigate channeling phenomena and particle acceleration in underdense plasmas. A fundamental understanding of these processes is of importance to the hole-boring fast ignition scheme for inertial confinement fusion. Proton probing was used to image the electromagnetic fields formed as the Omega EP laser pulse generated a channel through underdense plasma. Filamentation of the channel was observed, followed by self-correction into a single channel. The channel radius as a function of time was found to be in reasonable agreement with momentum- conserving snowplough models.